(untitled) (Journal of Bangladesh Academy of Sciences, 2018)
The aim of this study is to measure the feedback reactivity effects of the Bangladesh Atomic Energy Commission (BAEC) TRIGA Research Reactor (BTRR). Using digital instrumentation and control (I&C) system, feedback parameters such as reactivity coefficients of fuel, moderator and power effects are measured. At 300 kW reactor power, the obtained results for fuel temperature coefficient are 0.664 ꬿ/0c and 0.765 ꬿ/0c at C1 and D3 core positions respectively. The results for 100 kW to 400 kW reactor power show its increasing nature as the reactor power increases. The measured value of the moderator temperature coefficient is found to be 0.419 ꬿ/0c at 500 kW reactor power. The power coefficient of reactivity is measured for several power ranges from 50 kW to 2.5 MW and the average value is found to be 0.0757 ꬿ/kw. The measured values of the reactivity coefficients are found to be in a good agreement with the GA Safety Analysis Report (SAR) provided for BTRR. Journal of Bangladesh Academy of Sciences, Vol. 42, No. 2, 183-190, 2018